A borderland on the edge of materiality: ancient remains, storied landscapes, and community narratives from the arm of Finland. (3rd July 2021) - van den Berg, M.
ABSTRACT: In past decades landscapes have become recognized as essentially liminal systems: there has been an increased appreciation for the embeddedness of lived experiences of places in four-dimensional space-time and the landscape's connections with perceptions, stories, the material and immaterial pasts, as well as the material and immaterial present and future. Kilpisjärvi is such a place where immaterial pasts, presents, and futures consolidate into lived experiences. Intimate narratives of the local inhabitants and enveloping environment are produced through the intermingling of traditional ways of living and being with the development of modern perspectives and infrastructures. This photo essay glimpses at the flow of interconnected stories of becoming of an Arctic village's lifeworld. It glances at what has never been built nor written down, what has been built over, the local anecdotes that speak to these, and how this amalgamation of interweaving materiality and disembodiment shape an understanding of Kilpisjärvi and its inhabitants from an insiders and outsiders perspective. The essay takes the reader through the liminal landscapes of reindeer, reindeer herders, tourist organizations, and village life, and its analysis advances our understanding of how these all connect in a meshwork that teaches old and new ways of viewing the environment.